Mental health specialist video consultations for patients with depression or anxiety disorders in primary care: protocol for a randomised controlled feasibility trial - Tönnies, Justus; Hartmann, Mechthild; Wensing, Michel; Szecsenyi, Joachim; Friederich, Hans-Christoph; Haun, Markus W. (BMJ open, 2019)
Introduction Most people suffering from depression and anxiety disorders are entirely treated in primary care. Due to growing challenges in ageing societies, for example, patients’ immobility and multimorbidity, the transition to specialised care becomes increasingly difficult. Although the co-location of general practitioners and mental health specialists improves the access to psychosocial care, integrated in-person approaches are not practical for rural and single-doctor practices with limited personnel and financial resources. Treating primary care patients via internet-based video consultations by remotely located mental health specialists bears the potential to overcome structural barriers and provide low-threshold care. The aim of this randomised controlled feasibility trial is to investigate the feasibility of implementing of mental health specialist video consultations in primary care practices. - Methods and analysis Fifty primary care patients with significant depression and/or anxiety symptomatology will be randomised in two groups receiving either the treatment as usual as provided by their general practitioner or up to five video consultations conducted by a mental health specialist. The video consultations focus on (1) systematic diagnosis plus proactive monitoring using validated clinical rating scales, (2) the establishment of an effective working alliance and (3) a stepped-care algorithm within integrated care adjusting treatments based on clinical outcomes. We will investigate the following outcomes: effectiveness of the recruitment strategies, patient acceptance of randomisation, practicability of the technical and logistical processes related to implementing video consultations in the practices’ workflows, feasibility of the data collection and clinical parameters. - Ethics and dissemination This trial has undergone ethical scrutiny and has been approved by the Medical Faculty of the University of Heidelberg Ethics Committee (S-634/2018). The findings will be disseminated to the research community through presentations at conferences and publications in scientific journals. This feasibility trial will prepare the ground for a large-scale, fully powered randomised controlled trial. - Trial registration number DRKS00015812.